Women Behind Bars: Trends and Policy Issues - Kaplan, Mark S. (1996)
In the crusade to get tough on crime, policy makers have also gotten tough on women, drawing them into prisons in rapidly growing numbers. Today, incarcerated women are predominately poor, uneducated, and unskilled; are disproportionately African American and Latina young women with children; and have severe health and mental health problems. This article examines the characteristics and needs of these women and presents recommendations for their more humane and pragmatic treatment and for social policy that is relevant for the decarceration of this country's soaring female prison population